2021
DOI: 10.1093/jjco/hyab084
|View full text |Cite
|
Sign up to set email alerts
|

Survival of chemo-naïve patients with EGFR mutation-positive advanced non-small cell lung cancer after treatment with afatinib and bevacizumab: updates from the Okayama Lung Cancer Study Group Trial 1404

Abstract: Background In a phase I study, afatinib (30 mg/body daily) plus bevacizumab (15 mg/kg every 3 weeks) was well tolerated and showed favourable outcomes in patients with epidermal growth factor receptor (EGFR)-mutant advanced non-small-cell lung cancer. Herein, we report the 2-year progression-free survival, overall survival and safety profile of these patients. Methods Chemo-naïve patients with EGFR-mutant advanced non-small-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“… 13 16 A phase I clinical trial, the Okayama Lung Cancer Study Group Trial 1404, reported that the combination of afatinib and bevacizumab therapy was feasible and safe for the treatment of chemo-naïve advanced EGFR-mutated NSCLC patients. 17 In the same trial, afatinib combined with bevacizumab showed 24.2 months of PFS in chemo-naïve advanced EGFR-mutated NSCLC patients. 17 Another previous retrospective study showed that the combination of afatinib and bevacizumab had an 87.7% ORR and 23.9 months PFS as first-line therapy in advanced EGFR-mutated lung adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“… 13 16 A phase I clinical trial, the Okayama Lung Cancer Study Group Trial 1404, reported that the combination of afatinib and bevacizumab therapy was feasible and safe for the treatment of chemo-naïve advanced EGFR-mutated NSCLC patients. 17 In the same trial, afatinib combined with bevacizumab showed 24.2 months of PFS in chemo-naïve advanced EGFR-mutated NSCLC patients. 17 Another previous retrospective study showed that the combination of afatinib and bevacizumab had an 87.7% ORR and 23.9 months PFS as first-line therapy in advanced EGFR-mutated lung adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 98%
“… 17 In the same trial, afatinib combined with bevacizumab showed 24.2 months of PFS in chemo-naïve advanced EGFR-mutated NSCLC patients. 17 Another previous retrospective study showed that the combination of afatinib and bevacizumab had an 87.7% ORR and 23.9 months PFS as first-line therapy in advanced EGFR-mutated lung adenocarcinoma patients. 18 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many attempts have been made to investigate the combination of afatinib with bevacizumab for the first-line treatment of EGFR -mutated NSCLC. A manageable adverse event and a promising efficacy were observed in some early-phase clinical trials [ 18 , 19 ] and a satisfactory tolerability and treatment outcome were also reported in real-world patients [ 20 ]. Nevertheless, whether the combination of afatinib and bevacizumab presents a synergistic effect and, thus, outperforms the single-agent afatinib in a front-line setting, remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that afatinib at 30 mg/d was more tolerable than the dose of 40 mg/d, but favorable efficacy was maintained for Asian patients with NSCLC (18)(19)(20). However, evidence is sparse regarding the efficacy and safety of afatinib at 30 mg in the treatment of advanced LAD with uncommon EGFR mutations.…”
Section: Introductionmentioning
confidence: 99%